\[\boxed{\text{1197\ (1197).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ a^{5} - a^{4} - 16a + 16 =\]
\[= a^{4}(a - 1) - 16(a - 1) =\]
\[= (a - 1)\left( a^{4} - 16 \right) =\]
\[= (a - 1)\left( a^{2} - 4 \right)\left( a^{2} + 4 \right) =\]
\[= (a - 1)(a - 2)(a + 2)\left( a^{2} + 4 \right)\]
\[2)\ a^{2n}b^{2n} - b^{2n} - a^{2n} + 1 =\]
\[= b^{2n} \cdot \left( a^{2n} - 1 \right) - \left( a^{2n} - 1 \right) =\]
\[= \left( a^{2n} - 1 \right)\left( b^{2n} - 1 \right) =\]
\[= \left( a^{n} - 1 \right)\left( a^{n} + 1 \right)\left( b^{n} - 1 \right)\left( b^{n} + 1 \right)\ \]
\[\boxed{\text{1197.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ 0x + y = - 3\]
\[y = - 3 \Longrightarrow график\ d.\]
\[2)\ 2x - y = 1\ \]
\[y = 2x - 1\ \]
\[при\ x = 1 \Longrightarrow \ \ y = 2 - 1 = 1 \Longrightarrow \ \]
\[\Longrightarrow \ прямая\ c.\]
\[3)\ 3x + 0y = 6\ \ \]
\[3x = 6\ \]
\[x = 2 \Longrightarrow прямая\ b.\]
\[4)\ x + 2y = 0\]
\[2y = - x\ \ \]
\[при\ y = - 1 \Longrightarrow \ x = 2 \Longrightarrow \text{\ \ }\]
\[\Longrightarrow прямая\ a.\]